Sarcopenia and cardiovascular diseases: A systematic review and meta‐analysis - Xinrong Zuo; Xuehong Li; Kuo Tang; Rui Zhao; Minming Wu; Yang Wang; Tao Li (Wiley, 2023)
Abstract Sarcopenia is an age‐related disease and is often accompanied by other diseases. Now, many studies have shown that cardiovascular diseases (CVDs) may raise the incidence rate of sarcopenia. Therefore, the purpose of this study was to conduct a systematic review and meta‐analysis to investigate the prevalence of sarcopenia in patients with CVDs compared with the general population, defined as relatively healthy non‐hospitalized subjects. The databases of PubMed, Embase, Medline and Web of Science were searched for eligible studies published up to 12 November 2022. Two assessment tools were used to evaluate study quality and the risk of bias. Statistical analysis was conducted using STATA 14.0 and R Version 4.1.2. Thirty‐eight out of the 89 629 articles retrieved were included in our review. The prevalence of sarcopenia ranged from 10.1% to 68.9% in patients with CVDs, and the pooled prevalence was 35% (95% confidence interval [95% CI]: 28-42%). The pooled prevalence of sarcopenia was 32% (95% CI: 23-41%) in patients with chronic heart failure (CHF), 61% (95% CI: 49-72%) in patients with acute decompensated heart failure (ADHF), 43% (95% CI: 2-85%) in patients with coronary artery disease, 30% (95% CI: 25-35%) in patients with cardiac arrhythmia (CA), 35% (95% CI: 10-59%) in patients with congenital heart disease and 12% (95% CI: 7-17%) in patients with unclassed CVDs. However, in the general population, the prevalence of sarcopenia varied from 2.9% to 28.6% and the pooled prevalence was 13% (95% CI: 9-17%), suggesting that the prevalence of sarcopenia in patients with CVDs was about twice compared with the general population. The prevalence of sarcopenia was significantly higher only in patients with ADHF, CHF and CA compared with the general population. There is a positive correlation between CVDs and sarcopenia. The prevalence of sarcopenia is higher in patients with CVDs than that in the general population. With global aging, sarcopenia has brought a heavy burden to individuals and society. Therefore, it is important to identify the populations with high‐risk or probable sarcopenia in order to do an early intervention, such as exercise, to counteract or slow down the progress of sarcopenia.